2009
DOI: 10.1039/b818892k
|View full text |Cite
|
Sign up to set email alerts
|

Reductive quenching of pyridine linked porphyrins by phenol: a case of proton coupled electron transfer

Abstract: PCET is reported for free-base meso-(pyridyl)porphyrins, a pure organic system in dichloromethane solution, by employing UV/Vis and fluorescence spectroscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Isomeric 5,10,15,20- meso -tetrakis (pyridyl) porphyrins (TpyPs) (Chart ) are an analogue of H 2 TPP where the phenyl ring is replaced by pyridine to the meso -position of the porphyrin. The steady-state spectroscopic features are grossly similar to those of the model H 2 TPP molecule, , but TpyPs differ in electron-accepting capability in singlet excited state in sharp contrast to H 2 TPP molecule, which is known as a π-electron donor. For instance, in our earlier report, we have observed that TpyPs takes part in photoinduced reduction involving proton-coupled electron transfer reaction when an electron transferred from the phenol to the singlet porphyrin is coupled with the concerted motion of the bound proton to the associated pyridine.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Isomeric 5,10,15,20- meso -tetrakis (pyridyl) porphyrins (TpyPs) (Chart ) are an analogue of H 2 TPP where the phenyl ring is replaced by pyridine to the meso -position of the porphyrin. The steady-state spectroscopic features are grossly similar to those of the model H 2 TPP molecule, , but TpyPs differ in electron-accepting capability in singlet excited state in sharp contrast to H 2 TPP molecule, which is known as a π-electron donor. For instance, in our earlier report, we have observed that TpyPs takes part in photoinduced reduction involving proton-coupled electron transfer reaction when an electron transferred from the phenol to the singlet porphyrin is coupled with the concerted motion of the bound proton to the associated pyridine.…”
Section: Introductionmentioning
confidence: 72%
“…The steady-state spectroscopic features are grossly similar to those of the model H 2 TPP molecule, , but TpyPs differ in electron-accepting capability in singlet excited state in sharp contrast to H 2 TPP molecule, which is known as a π-electron donor. For instance, in our earlier report, we have observed that TpyPs takes part in photoinduced reduction involving proton-coupled electron transfer reaction when an electron transferred from the phenol to the singlet porphyrin is coupled with the concerted motion of the bound proton to the associated pyridine. Hence, this molecule is found to be a potentially important mimic system to better understand activity in biology, in particular in photosynthesis, where tyrosine H-bonded to histidine participates in the PCET process in photosystem II, which is a porphyrin-based complex.…”
Section: Introductionmentioning
confidence: 99%
“…[4,[35][36] This was followed by extensive studies by Wenger et al on ground state and excited state PCET between the complexes of d 6 metal ions viz, Ru(II), Ir(II) having pyridylimidazole ligands with protonable and deprotonable chemical groups and various simple molecules such as 1,4-benzoquinone, pyridine or 3,5-dinitrobenzene as the quenchers. [31,[37][38][39][40][41] Mechanistic studies indicated the possibility of both unidirectional PCET as well as counterdirectional PCET processes. Such directionality of the PT and ET reactions is an important aspect of ES-PCET for their useful deployment in various applications.…”
Section: Introductionmentioning
confidence: 99%
“…were developed by several groups [57][58][59][60][61][62][63][64][65]. Such a strategy is interesting since it prevents diffusional issues by linking the excited state was lastly reported to be Δε = −10000 M -1 cm -1 at 452 nm [41], resulting in a huge signal bleach observed in the blue side of visible region after flashing the compound with a laser.…”
Section: Methodsmentioning
confidence: 99%